The effec of Neurotensin on intestinal ischemia reperfusion injury - Emin GÜRLEYİK and Günay GÜRLEYİK and İrfan CAN and Ali ÖZCAN and Pembegül GÜNEŞ and İlhan ONARAN (Turkish Journal of Gastroenterology, 2019)
-